Associated risk factors, maternal and fetal outcomes of caesarean delivery in four health facilities in Littoral Region, Cameroon: A cross-sectional study - Thomas Obinchemti Egbe; Theophile Kefeyin Keney; Elvis Temfack (Journal of Midwifery & Reproductive Health, 2020)
Background & aim: The caesarean rate is on the rise in Cameroon; nonetheless, there is a paucity of data regarding its associated risk factors and outcomes.  This study aimed to determine the associated risk factors, as well as maternal and fetal outcomes of caesarean delivery in four hospitals in Cameroon. Methods: This cross-sectional study was conducted on 1322 parturient women who gave birth in one tertiary, two secondary, and one primary healthcare facility in Cameroon within March 2015-February 2016. Maternal and fetal data were obtained by interviewer-administered pretested questionnaires. Univariate and multivariate analyses with Chi-square and Fischer's exact tests compared outcomes between caesarean and vaginal births. Results: Referral from one hospital to another (AOR 2.83; 95% CI: 2.09-3.84) and antimicrobial use during labor and delivery (AOR 11.0; 95% CI: 7.6-17) were maternal factors independently associated with caesarean delivery. Postpartum hemorrhage of 1000-1500 mL (AOR 9.7; 95% CI: 1.7-55), maternal fever (AOR 3.5; 95% CI: 1.4-9.2), and prolonged hospital stay (AOR 3.8; 95% CI: 3.2-4.4) were maternal complications independently associated with caesarean delivery. Furthermore, birth asphyxia (AOR 2.1; 95% CI: 1.3-3.6), respiratory distress (AOR 4.7; 95% CI: 1.6-12.4), and neonatal sepsis (AOR 3.2; 95% CI: 1.5-6.9) were fetal complications independently associated with caesarean delivery. Conclusion: There were more referrals from another facility, intrapartum antimicrobial use, hemorrhage, maternal fever, prolonged hospital stay including birth asphyxia, neonatal sepsis, and respiratory distress among caesarean delivery.